Impacts of solar energy projects in rural areas - A case study in Kenya - Mohajer, Christoffer; Göras, Anna (My University, 2016)
Currently there are around 1.3 billion people in the world living without access to electricity and about half of them live in Africa. The majority of these Africans without access to electricity live in rural areas and to overcome this issue rural electrification by solar photovoltaic (PV) has emerged as one of the possibilities to alieve this energy poverty. This is a case study researching two different off grid solar PV projects in Kenya, a microgrid in Sidonge A’ and Solar Home Systems (SHS) in the rural areas surrounding Bungoma/Kitale. The aim of this case study was to do an impact assessment of gaining access to electricity via microgrids and SHS and to find out what differences there were in impacts between them. A case study approach was chosen where semi-structured interviews and observations from a field study was the input method into rural sustainability indicators that were compared with pre-electricity indicators. The rural sustainability indicators of the different solar PV systems were also compared with each other to help answer the aim of this study. The results showed that access to off grid electricity had positive effects related to health, safety, economy, education, mobile phone and internet usage. The differences between the different off grid electricity solutions were that SHS had less environmental impact and was cheaper to use, however microgrids had positive impacts regarding business investments, gender equality and social activities which Solar Home Systems did not have.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering